The Role of Financial Literacy, Financial Attitude on Financial Skill Management for Housewives - Desi Fatmala; A. Asriani; Abid Ramadhan (Manunggal Halim Jaya, 2026)
Understanding financial literacy involves recognizing and managing various financial aspects, including saving, investing, debt management, understanding product insurance, and utilizing financial instruments for personal use. Homemakers, as the primary party responsible for managing the family's finances, sought to improve their literacy and financial stability, accompanied by a prudent financial attitude. This research aims to analyze the influence of literacy, finances, and attitudes on financial skills in the Mother House ladder, specifically in managing finances, in Masiku Village, District Towuti, Regency East Luwu, Indonesia. The approach used is a descriptive study, conducted as a quantitative study, encompassing all households in the area, including those at Mother House. A total of 201 respondents were included in the sample through a non-probability sampling method with a purposive sampling technique. Data collection was carried out through descriptive analysis, validity and reliability tests, and multiple linear regression analysis, which included the T-test (partial test), F-test (simultaneous test), and coefficient test determination (R²). The findings of this study disclose that Good literacy and financial attitude have a significant influence on skills related to managing finances in Masiku Village, District Towuti, Regency East Luwu.